Monitoring of the relief changes in polygonal peat plateaus adjacent to the highway Zapolyarnoe — Tazovsky - E. M. Babkin; E. A. Babkina; M. O. Leibman; R. R. Khayrullin; A. V. Khomutov; Е. М. Бабкин; Е. А. Бабкина; М. О. Лейбман; Р. Р. Хайруллин; А. В. Хомутов (Arctic and Antarctic Research, 2022)
The thawing of polygonal ice wedges determines the dynamics of polygonal peatland relief. The polygonal peat plateaus in the Pur-Taz interfluve account for an average of 6,5 % of the total area. The purpose of the proposed study is to establish the short-term rates and direction of change in the plateaus’ relief under the combined action of technogenic and natural factors, using monitoring data for the period 2005–2022. Based on satellite images and orthophotoplans, elements of the peat plateaus have been outlined and their areas have been determined for different time slices. The studies were carried out on a peat plateau immediately adjacent to the highway (T1) and on a background peat plateau at a distance of about 1.5 km from the highway (T2). To identify the natural causes of changes in the relief of the peat plateaus, the influence of climatic parameters is considered. The rates of relief change in natural conditions and under the impact of the highway are also compared. It has been established that in the area to the north-west of the highway the relief of the T1 polygonal peat plateau has stabilized. In the south-east section of T1, degradation has sharply increased after the construction of the highway. Due to the degradation of the polygons, the polygonal troughs expanded. In the background peat plateau T2, the rate of relief degradation is somewhat higher than in the northwestern portion of T1. Comparison of the main climatic parameters and degradation rates of the polygonal relief did not show any clear correlations. Probably, of greater importance are the regime of atmospheric precipitation, the redistribution of surface runoff and recurrence of flooding and drainage of the polygonal troughs, determined by the rhythmic course of the relief degradation. Вытаивание полигонально-жильных льдов (ПЖЛ) определяет динамику рельефа полигональных торфяников. Массивы полигональных торфяников Пур-Тазовского междуречья составляют в среднем 6,5 % от общей площади. Целью исследования является установление ...